PREDICTION SCORE IN SURGICAL COMPLICATIONS ESTIMATION IN THE PRACTICE OF INTERNIST - D. P. Kotova; S. V. Kotov; M. Yu. Gilyarov; V. S. Shemenkova (Кардиоваскулярная терапия и профилактика)
Recently, development of medicine leads to the increase of the number and complexity of surgical interventions, explaining high significance of the risk assessments for postsurgical complications and probability of fatal outcome; this requires participation of internist in patients management with correction of therapy. The article is focused on the main scores and indexes utilized in clinical practice for prediction of possible complications, incl. cardial. A detailed description provided, for every calculator, features and limitations for usage and results interpretation.